1987
DOI: 10.1093/brain/110.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis in North-East Scotland an Association With Hla-Dow1

Abstract: This study reports the frequencies of HLA antigens and the polymorphic variants of C4, C2, and Bf for 200 patients with multiple sclerosis (MS) living in the Grampian region of Scotland, an area of high disease prevalence. A group of 128 normal subjects from the same region were typed for comparison. Although the frequencies of HLA-B7 and DR2 in the patient group (43.3% and 49.4%, respectively) were found to be similar to those reported for other Northern European HLA studies on patients with MS, high frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…This study also found that HLA-DR2 was associated with relapsing MS but not patients with progressive MS; however, PPMS and SPMS patients were grouped together (Francis et al, 1987).…”
Section: Human Leukocyte Antigensmentioning
confidence: 53%
“…This study also found that HLA-DR2 was associated with relapsing MS but not patients with progressive MS; however, PPMS and SPMS patients were grouped together (Francis et al, 1987).…”
Section: Human Leukocyte Antigensmentioning
confidence: 53%
“…In Arabian (38) as well as in Sardinian (39) MS patients an association with the DR4 antigen has been found. A weak association with the DQwl antigen (DR2 associated) was found in Scottish MS patients (11), but this finding has not been confirmed (12,40). An association with the DPw4 specificity has been reported in Swedish MS patients (41).…”
Section: Discussionmentioning
confidence: 90%
“…It has been proposed that PCP MS and R/R MS may be separate disease entities (6) since they differ with respect to epidemiology (6), age at onset (4, 5, 7), initial symptoms (4,6), prognosis with regard to degree of disability (4,7) and to mortality (8), and response to immunosuppression (9). Efforts to differentiate between PCP MS and R/R MS by serological HLA class II typing have yielded divergent and inconclusive results (10)(11)(12) (16)(17)(18).…”
mentioning
confidence: 99%
“…The presence of a genetic component in the etiopathogenesis of multiple sclerosis (MS) has been frequently hypothesized on the basis of (1) family studies showing an increased prevalence of the disease among relatives of patients compared to the general population [1,2], (2) a higher concordance among monozygotic than dizygotic twins [3][4][5][6], and (3) the associations between MS and HLA antigens [7][8][9][10][11],…”
Section: Introductionmentioning
confidence: 99%